2016
DOI: 10.3389/fmicb.2016.00982
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-Cutaneous Leishmaniasis Co-infection: Influence on Disease Outcomes and Immune Response

Abstract: Malaria and Cutaneous Leishmaniasis (CL) are co-endemic throughout large regions in tropical countries and co-infection may impact the evolution of host-parasite interactions. In the present study, we evaluate Malaria/Leishmaniasis disease outcome, Th1/Th2 cytokine levels and the CD4 and CD8 T-cell profiles in a co-infection murine model (BALB/c) of Plasmodium yoelii 17XNL (Py) and Leishmania amazonensis (La) or L. braziliensis (Lb). Malaria parasitaemia was assessed through blood strains stained with Giemsa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 64 publications
0
23
1
1
Order By: Relevance
“…Seven experimental studies assessed Plasmodium coinfection and TL [ 53 59 ]. In coinfection models of Plasmodium yoelii or Plasmodium berghei together with Leishmania enrietti , L .…”
Section: Resultsmentioning
confidence: 99%
“…Seven experimental studies assessed Plasmodium coinfection and TL [ 53 59 ]. In coinfection models of Plasmodium yoelii or Plasmodium berghei together with Leishmania enrietti , L .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous studies has found patients suffering from malaria infections exhibit the presence of Leishmania parasites in their body [55] or vice versa [16, 17]. The outcome of malaria infections can be altered according to the Leishmania species involved [19]. When both malaria and leishmaniasis are present in humans, it affects the disease outcome and progression of disease due to the modulation of the immune response [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of malaria infections can be altered according to the Leishmania species involved [19]. When both malaria and leishmaniasis are present in humans, it affects the disease outcome and progression of disease due to the modulation of the immune response [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em humanos a hipergamaglobulinemia, leucopenia, tosse seca, quadros febris, anemia e hepatoesplenomegalia são as características cardeais da sintomatologia de leishmaniose visceral, sendo que nas situações em que a doença progride acentuadamente podem ser observados episódios de anemia, pancitopenia, emagrecimento progressivo, diarreia, icterícia, vômito e edema periférico, além de eventuais comorbidades infecciosas em pacientes com malária ou portadores do vírus HIV (PASTORINO et al, 2002;DESJEUX e ALVAR, 2003;QUEIROZ et al, 2004;SILVA et al, 2008;OLIVEIRA et al, 2010;LINDOSO et al, 2016;PINNA et al, 2016). LEE et al, 2002;PASCALIS et al, 2003;SILVA-ALMEIDA et al, 2012;AGALLOU et al, 2017).…”
Section: Convém Citar Que Os Gêneros Crithidia Blastocrithidia Leptunclassified